Intrinsic motivation on employee engagement with self-efficacy as mediating variables - Cely Okta Wirsi; Mega Asri Zona (Universitas Negeri Padang, 2022)
The purpose of this study is to analyze : (1) the effect of intrinsic motivation on employee engagement (2) the effect of intrinsic motivation on self-efficacy (3) the effect of self-efficacy on employee engagement (4) the effect of intrinsic motivation on employee engagement through self-efficacy. This study uses a causal research design. This study used a population of 42 civil servants from the Department of Manpwer and Industry of Padang City. This study uses total sampling, which means that the total sample was the same as the total population of 42 people. Data were collected using a questionnaire with a Likert scale. This study uses data analysis techniques using SPSS 25 software. The results of data processing show that : (1) intrinsic motivation has a positive and significant effect on employee engagement at the Department of Manpwer and Industry of Padang City (2) intrinsic motivation has a positive and significant effect on self-efficacy at the Department of Manpwer and Industry of Padang City (3) self-efficacy has a positive and significant effect on employee engagement at the Department of Manpower and Industry of Padang (4) intrinsic motivation has a positive and significant effect on employee engagement through self-efficacy at the Department of Manpwer and Industry of Padang City.